Motivation is the Strongest Influence in Choosing Delivery Place: Motivasi adalah Faktor yang Paling Kuat Memengaruhi Pemilihan Tempat Persalinan - Indria Astuti; Dany Hilmanto; Budi Handono (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective: To analyze the factors that correlated with decision to choose the most appropriate delivery place of mothers’ delivery attended by health personnel, in West Bandung District. Method: This was a case-control study with consecutive sampling method on the mothers who gave birth at two health centers: Cikalong Wetan and Cipongkor, West Bandung District. There were two groups of mothers. First, the case group consisted of 52 mothers at non-healthcare facilities. Second, control group consisted of 52 mothers at healthcare facilities. There were sociodemographic (culture, educational), contextual (income, transportation, distance, availability health facilities) and characteristics of needs (counseling, prenatal care, motivation) factors and dependent variable was decision in choosing the place of delivery. The data was analyzed using chi square test to determine the correlation factors, whereas multiple logistic regression was used to determine the strongest correlating factors. Result: The results showed that there were correlation between various factors with the decision selection of delivery place of the mothers by health care in: cultural factor (OR = 23; p < 0.001; CI 95% : 7.99-66.20), educational factor (OR = 4.86; p < 0.001; CI 95% : 1.35- 19.09), income factor (OR = 2.36; p = 0.031; CI 95%: 6.51-57.49), transportation factor (OR = 19.35; p < 0.001; CI 95%: 6.51 to 57.49), distance factor (OR = 3.19, p = 0.007; 95% CI: 1.67-37.69), availability health facilities factor (OR = 7.94, p = 0.007; CI 95% 1.67-37.69 and OR = 3.97; CI 95% : 0.40-39.75), counseling factor (OR = 23, p < 0.001; CI 95%: 7.99-66.20), prenatal care factor (OR = 5.21, p < 0.001; 95%: 2.24-12.12), motivational factor (OR = 196, p < 0.001; CI 95 % : 41.64-922.48). The strongest factor was the motivational factor (OR = 103.33; p < 0.001; CI 95%: 10.00-1065.72). Conclusion: This study concluded that there was correlation between sociodemographic, contextual, and characteristics of needs with the decision in choosing place of delivery that attended by health personnel. Motivation was the strongest factor correlated to the mothers’ decision to deliver at public health center. Keywords: characteristics of demand, contextual, delivery place, socio-demographic